REPETITION, EMOTION, MEMORY - van Ommen, Clifford; Painter, Desmond (PINS-Psychology in Society, 2026)
In this article we attempt to articulate a self that is marked by repetition, a notion that seeks to take seriously the lack of metaphysical foundations in social, psychological and ethical life; that seeks to counter those understandings that hope to escape the ravages of time and the unexpected movements of life. After presenting a poststructuralist reading of the Kierkegaardian notion of repetition in relation to the thorny problem of the self, we attempt, first, to substantiate this self through a reading of emotion and memory as deeply socially embedded and as not pre-social and natural, and secondly, to develop an understanding of repression as an essential feature of life that does not infer distortion or denial. At this point we will introduce the notion of replacements. Replacements, as a feature of this form of repression, are culturally valid narratives that respect the particularities of memory and draw the person in as an embodied thinker. We illustrate this understanding of the self by delineating a role for psychotherapy as a place where the sculpting of such replacements may take place, thus enabling persons to continue with the ethical task of achieving a self.